(3GdCMRGH aj dHfGf hCKQgG aj GdJQHjI NdGd GdMQH GdCgdjI (B1975-1990s - (3gdGd, gdG fGjas ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2004)
(3EfWdbJ gPg GdOQGSI ef ETcGdjI GdMQH GdCgdjI aj dHfGf hCKQgG aj GdJQHjI YGeI hYdi GdfGTFI hTNUjI GdJdejP hJhLjggG HTcd NGU(B. (3EYJeOJ GdOQGSI Ydi GdaQVjI GdJGdjI(B: (3GdOhQ GdSdHj deeGQSI GdCMRGH aj GdMQH GdCgdjI aj dHfGf aj ejOGf GdJQHjI hGdGbJUGO, eMGhdI GdcTa Yf(B: 1) (3EOGQI GdeDSSGJ GdJQHhjI GdQSejI hGdNGUI aj GdfRGYGJ GdYScQjI hSdHjGJgG NdGd GdMQH GddHfGfjI GdCgdjI(B. 2) (3EOGQI GdeDSSGJ GdGbJUGOjI GdQSejI hGdNGUI aj GdfRGYGJ GdYScQjI ef bHd GdejdTjGJ (B1975-1990. 3) (3eeGQSGJ GdCMRGH GdJj JQcJ hChQKJ fJGFL SdHjI aj LejY GdejGOjf GdJQHhjI hGdGLJeGYjI hGdGbJUGOjI(B. (3dEKHGJ aQVjI GdOQGSI Jqe GdJWQb deeGQSGJ GdCMRGH GdSjGSjI aj dHfGf NdGd SfhGJ GdMQH aj GdeDSSGJ hNGQLgG, hcja CKQJ SdHG Ydi GdMjGI GdJQHhjI hGdGbJUGOjI hGdGLJeGYjI, HGdEVGaI Edi eMGhdI GdHMK hGdETGQI dhGbY GdMhGOK GdCSGSjI GdJj MUdJ CKfGA GdMQH, hCge eG UOQ ef HjGfGJ hNWGHGJ hfTGWGJ ddCMRGH, hcja JMqhdJ eeGQSJgG Edi WGFajI hYScQjI hCNPJ GdWGHY GdYScQj GdWGFaj(B. (3ceG YGOJ GdOQGSI CjVG Edi eHGOF GdCMRGH GdJj TGQcJ aYdjG HejdjTjGJgG HYedjGJ GdMQH hGdJOejQ debGQfI GdeeGQSGJ eY GdeHGOF Ydi GdCQV(B. (3ceG Jqe GdONhd Edi HYV GdeOGQS hGdKGfhjGJ hGdbjGe HHYV GdebGHdGJ eY eOQGFgG, hOQGSI hVY gPg GdeOGQS NdGd GdMQH hYdGbI GdCMRGH HEOGQJgG hGdgjFI GdJYdjejI hGdJdGePI(B. (3HGdEVGaI Edi ebGHdI HYV QLGd GdCMRGH hcja cGfJ eTGQcJge HGdMQH, hHYV GdhRQGA eef TZdhG efUH hRjQ JQHjI hPdc dJHjGf JCKjQ GdMQH Ydi GdeDSSGJ GdJQHhjI hcja CKQJ eeGQSGJ GdCMRGH aj cd ejGOjf GdJQHjI hGdGbJUGO hGdMjGI GdGLJeGYjI(B. (3ceG JqeJ GdETGQI Edi JgOje GdeOGQS GdfGJL Yf eeGQSGJ gPg GdCMRGH GdYScQjI, hcja MhdJ HYVgG Edi KcfGJ YScQjI JGHYI dejdjTjGJgG(B. (3hNJeJ GdOQGSI HYQV dCKQ gPg GdeeGQSGJ Ydi GdhVY GdGLJeGYj ddoCSQ MjK MQe GdcKjQ ef GdChdGO ef GSJceGd GdOQGSI(B.s
(3GdfhY (B: (3CWQhMIs
Keywords: Civil War; Education & Politics; Education & Politiques; Guerre Guerre Civile; War; (3GdMQH GdMQH GdGgdjIs; (3GdSjGSI hGdJYdjes